Photocurrent Enhancement of Dye-Sensitized Solar Cells owing to Increased Dye-Adsorption onto Silicon-Nanoparticle-Coated Titanium-Dioxide Films - Ha, Eun-Sung; Yoo, Beomjin; Baik, Hionsuck; Lee, Yeonhee; Kim, Kang-Jin (WILEY-V C H VERLAG GMBH, 2012)
The inverse-micellar preparation of Si nanoparticles (Nps) was improved by utilizing sodium naphthalide. The Si Nps were subsequently functionalized with 4-vinylbenzoic acid for their attachment onto TiO2 films of dye-sensitized solar cells (DSSCs). The average diameter of the COOH-functionalized Si (Si?COOH) Nps was 4.6(+/- 1.7) nm. Depth profiling by secondary-ion mass spectrometry revealed that the Si Nps were uniformly attached onto the TiO2 films. The number of RuII dye molecules adsorbed onto a TiO2 film that was treated with the Si?COOH Nps was 42?% higher than that on the untreated TiO2 film. As a result, DSSCs that incorporated the Si?COOH Nps exhibited higher short-circuit photocurrent density and an overall energy-conversion efficiency than the untreated DSSCs by 22?% and 27?%, respectively. This enhanced performance, mostly owing to the intramolecular charge-transfer to TiO2 from the dye molecules that were anchored to the Si?COOH Nps, was confirmed by comparing the performance with two different RuIIbipyridine dyes (N719 and N749).
Keywords: GERMANIUM NANOCLUSTERS; NANOCRYSTALLINE TIO2; CONVERSION; EFFICIENCY